Effect of Different Weed Management Practices on Rainy Season Maize Under Stale Seedbed Condition at Puranchur, Kaski - Tandon, Sansar; Parajuli, Tulsi; Marasini, Dinesh (Journal of Agriculture and Forestry University, 2026)
A field experiment was conducted at Puranchaur, Kaski during April to August, 2023 to evaluate the effect of different weed management practices on weed dynamics and yield of maize. The experiment was laid out in Randomized Complete Block Design (RCBD) with five weed management practices (manual weeding, farmers practice, sunhemp-coculture, tembotrione, and atrazine fb tembotrione) and three replications. The cultivar used was Rampur Hybrid 10. Data was recorded and analyzed using R-Studio. The experimental findings indicated that the plant height (258.25) and Leaf Area Index (LAI) (3.90) of maize was highest in Farmers` practices. Atrazine followed by Tembotrione at 21 days after sowing was found most effective in lowering weed density and weed dry weight. Yield (5720.59 kg/ha) and yield attributing character was also found higher in Atrazine followed by Tembotrione among all weed management practices. Results revealed that no weed management in Maize in rainy season under stale seedbed at Puranchaur, Kaski leads to reduction of yield by 40.50%.